Four years of low dose enzalutamide for metastatic castration-resistant prostate cancer - Gilles Natchagande, G; Vinh-Hung, Vincent (Klinicka onkologie, 2021)
BACKGROUND: The management of metastatic castration-resistant prostate cancer involves second-generation antiandrogen therapy, including enzalutamide. The recommended dose of 160mg/day is sometimes difficult to use in elderly patients because of the burden of comorbidities. The usefulness of a low effective dose remains unclear. METHODS: We report the first ever patient, now aged 87 years, who had progressing prostate cancer and was treated at 25% of the recommended dose for over 4 years. RESULTS: The most striking observation is that nothing extraordinary happened. The disease responded without dramatic toxicities. His follow-up has been serene on both aspects of prostate cancer and general health. CONCLUSION: Cautious dosage can have a long-lasting favorable impact in the elderly patient.
Keywords: prostatektomie; senioři nad 80 let; Benzamides; enzalutamide; reduced-dose drug use; Prostatic Neoplasms, Castration-Resistant; výsledek terapie; prostate cancer; treatment efficacy; mužské pohlaví; Kallikreins; nádory prostaty rezistentní na kastraci; Phenylthiohydantoin; benzamidy; prostatický specifický antigen; treatment outcomes; Antineoplastic Agents; fenylthiohydantoin; Prostate-Specific Antigen; Aged, 80 and over; kalikreiny; protinádorové látky; castration-resistant; Humans; Prostatectomy; prostatic neoplasms; nitrily; Treatment Outcome; lidé; Male; Nitriles